Stigma of psychological disorder among university students attending psychological counseling units: a field study - Ahmad , Ruqaia; Wadaa, Najlaa (Al-Adab Journal, 2024)
The current study aims to identify the stigma of psychological disorder among students attending psychological counseling units and to identify the stigma of the disorder according to gender variables (male/female). Academic specialization (scientific/humanitarian) and severity (mild, moderate, severe). To achieve the objectives of the study, the descriptive approach was adopted, and a questionnaire was prepared for this purpose. The psychometric properties of the questionnaire were verified, and the questionnaire was applied to a purposive sample of students attending psychological counseling units, numbering (60) male and female students, from both specializations. The results of the research indicated the following: Students attending psychological counseling units suffer from the stigma of psychological disorder. There are no statistically significant differences according to gender (males and females) in social stigma. There are no statistically significant differences according to academic specialization (scientific and humanities) in the stigma of psychological disorder, and there are differences in stigma according to the severity of the problems the student suffers from. In light of these results, a set of recommendations were developed for the competent authorities and a number of proposals for future research.